(untitled) (E Global Congress, 2023)
This article explores the imperative need for improving the accounting practices within household service entities. Household service entities encompass a diverse range of businesses, including cleaning services, lawn care providers, and personal chefs, among others. These entities often face unique challenges in their accounting processes, primarily due to the decentralized nature of their operations and the prevalence of cash transactions. Inadequate accounting practices can result in financial inefficiencies, tax compliance issues, and hindered growth potential. Through an in-depth analysis of the specific challenges faced by household service entities, this article proposes innovative strategies and best practices to enhance their accounting procedures. By embracing technology, implementing standardized accounting methods, and prioritizing transparency, household service entities can streamline their financial operations, improve decision-making, and foster sustainable growth. This article serves as a valuable resource for business owners, accountants, and policymakers seeking to enhance the financial management of household service entities.